Effects Of Globalization On Tourism Development In Vietnam - Dao, Truong Thi Xuan; Duyen, Nguyen Thi Kim; Vi, Nguyen Lam Ngoc; Sukana, Made (JURNAL DESTINASI PARIWISATA; Vol 10 No 2 (2022): VOL 10, NO 2 (2022): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2022)
Tourism is one of the typical examples of globalization. This paper aims to analyze and assess how globalization has impacted tourism development in Vietnam. Analyzing the positive and negative impacts of globalization on tourism development will provide an overview of what is happening in the context of Vietnam becoming one of the Asia countries having the highest tourism growth today. To take advantage of the positive effects of globalization in tourism development and minimize the negative impacts that globalization brings, Vietnam needs to have sustainable tourism development orientations. Keywords: Vietnam Tourism, Tourism Development, Globalization.